ANALISIS REDAMAN (LOSS) RATA-RATA PADA JARINGAN FTTH DI BTR BLOK O BEKASI - Ramdhany Rino Syahputra; Muhamad Bagaswara; Dian Budi Santoso (Politeknik Harapan Bersama Tegal, 2021)
Abstract The development of technology in modern times is growing very fast. Very increasingly sophisticated technology, the human need for data rates is very high to balance this technology. So that PT. TELKOM INDONESIA made a network design in the form of Fiber To The Home using fiber optic cable as the transmission system. The design of Fiber To The Home is a network from the center to the customer with mapping int the form of distance, device placement, device specifications, and how many devices will be used. The design result show that the design for the BTR Blok O Bekasi area uses 1 ODC, 23 ODP, and 72 customers. The average total attenuation analysis using the link budget calculation shows 20,3064159 dB for distribution 1 and 20,52062 dB for distribution 2. This attenuation is in accordance with the standarization that has been implemented by PT. TELKOM INDONESIA 28 dB.